Competency Develop Guideline for Operational Employees in Industrial Estate in Chonburi Province - Paechon, Anataya; Chunhasiwong, Kitti (Interdisciplinary Academic and Research Journal, 2023)
The necessity of a profession calls for workers to have the knowledge, skills, and expertise in specific fields. the ability to communicate Together with the development of cooperation among countries in the ASEAN region (AC), the competition between skilled workers has increased. from the above changes, the researcher is interested in studying human resource development in organizations in the eastern region. Chonburi Province is a province that promotes the eastern economy (EEC) The objectives of this research are 1) to study the current performance of operational employees in an industrial estate in Chonburi Province. 2) to study the expected performance of operational employees in an industrial estate in Chonburi Province. 3) to present a guideline for developing the competency of operational employees in an industrial estate in Chonburi Province. A group of 400 people used Taro Yamane's ready-made table. The research tool was a questionnaire with a reliability of 0.95. Data were analyzed for frequency, percentage, mean, and standard deviation. and interview form by bringing the information obtained from the interview to compile, analyze and summarize the results to be used as a guideline for developing the competency of operational employees in an industrial estate in Chonburi Province. The results of the research were as follows: 1) the current competency of operational employees in an industrial estate in Chonburi Province; Overall and each aspect was at a high level. Sorted are: characteristics, skills, and knowledge 2) expected competencies of employees at the operational level in an industrial estate in Chonburi province. Overall and each aspect was at a high level. Sorted are: in terms of characteristics, skills, and knowledge. 3) Guidelines for developing the competency of employees at the operational level in an industrial estate in Chonburi Province. In terms of knowledge, there are development guidelines that should provide training to provide knowledge about the nature of the assigned work. Skills have guidelines for development, that is, training and practice should be provided regularly to develop skills in analyzing and managing work data. basic computer program skills in practice and features There is a development approach, that is, the organization should find a way to build morale. Motivate Creativity should be developed. Learning and controlling one's emotions while working effectively.